2015
DOI: 10.1039/c4ra15384g
|View full text |Cite
|
Sign up to set email alerts
|

Advances in direct C–H arylation of 5,5- 6,5- and 6,6-fused-heterocycles containing heteroatoms (N, O, S)

Abstract: This report aims to review the advances made in C–H arylation of 5,6, 6,6 and 5,5 fused-heterocyclic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 163 publications
(94 reference statements)
0
38
0
Order By: Relevance
“…Based on the study by Chavez et al, the herein reported conditions in mesitylene appeared promising also for the copolymerization of 5‐BTz . However, neither the conditions of entries 1–5 nor variations involving co‐catalysts such as CuI, Cu(OAc) 2 or Ag salts did lead to coupling of NDIBr 2 and 5‐BTz (Table S1 supporting information) , …”
Section: Resultsmentioning
confidence: 77%
“…Based on the study by Chavez et al, the herein reported conditions in mesitylene appeared promising also for the copolymerization of 5‐BTz . However, neither the conditions of entries 1–5 nor variations involving co‐catalysts such as CuI, Cu(OAc) 2 or Ag salts did lead to coupling of NDIBr 2 and 5‐BTz (Table S1 supporting information) , …”
Section: Resultsmentioning
confidence: 77%
“…Accordingly, numerous synthetic methods for these scaffolds have been well established, including ring annulation and intermolecular cross-coupling. [19][20][21][22] Although a number of medicinal agents based on pyrrolo [1,2-a]pyrazine, another N-fused heterobicyclic system, have been disclosed in the literature, synthetic approaches to prepare this scaffold have been relatively underdeveloped, which prompted us to investigate the chemistry of pyrrolo [1,2-a]pyrazine. In this context, we have been involved in the design and synthesis of new chemical spaces based on the pyrrolo[1,2-a] pyrazine core (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…5 Since that time, numerous studies on their synthesis, properties, and applications have been published, which have been partially collected in earlier reviews. Synthetic strategies leading to indolizines possessing additional exocyclic conjugated C-C double or triple bonds, as well as functionalization of the indolizine core 7 have been omitted here for the sake of brevity. The number of valuable contributions pressed us to be selective.…”
Section: Introductionmentioning
confidence: 99%